Case/Lang/Veirs [compact disc] - Case, Neko; Lang, K. D. (Kathy Dawn), 1961-; Veirs, Laura (ANTI-, 2016)
A true collaboration between three phenomenal, self-driven artists: avant-rock icon Neko Case, legendary musical nomad K.D. Lang, and indie folk star Laura Veirs. The women wrote all fourteen songs and shared lead vocals equally, sometimes even within the same track.